Knowledge Transfer in Erp Implementation: Universitas Islam Indonesia Story - Fitriati Akmila (Jurnal Aplikasi Bisnis, 2017)
Enterprise resource planning (ERP) is an integrated software application in enterprise system that is used to manage organizations resources. Currently, SAP is the most widely used of ERP systemi package in the market.This paper is a case study based on the ERP implementation at the Universitas Islam Indonesia (UII) in Yogyakarta, Indonesia. This study sees ERP implementation in knowledge transfer perspective in which explains the process of bringing explicit business processes to the organization.There are four stages in understanding the knowledge transfer process at UII: initiation, implementation, ramp up, and integration. The most crucial stages are ramp up and integration. During the ramp up organization adopt the "best processes" by configuring their environment so that explicit knowledge are easily transferred to the organization. In the integration, the knowledge is internalized into the organization and seen as agradual processforthe new practices to become part of the new reality of the organization.